An Index of Risk as a Measure of Biodiversity Conservation Achieved through Land Reform - SUSAN WALKER; ROBBIE PRICE; R.T. THEO STEPHENS (Conservation Biology, 2008)
We measured the net progress of land reform in achieving a national policy goal for biodiversity conservation in the context of ongoing clearing of native vegetation and additions of land to a highly nonrepresentative (residual) reserve network, interior South Island, New Zealand. We used systematic conservation‐planning approaches to develop a spatially explicit index of risk of biodiversity loss (RBL). The index incorporated information from national data sets that describe New Zealand's remaining indigenous land cover, legal protection, and land environments and modeled risk to biodiversity on the basis of stated assumptions about the effects of past habitat loss and legal protection. The index identified irreplaceable and vulnerable native habitats in lowland environments as the most at risk of biodiversity loss, and risk was correlated with the density of threatened plant records. To measure achievement, we used changes in the index that reflected gains made and opportunity costs incurred by legal protection and privatization. Application of the index to measure the difference made by land reform showed it had caused a net increase in the risk of biodiversity loss because most land vulnerable to habitat modification and rich in threatened plant species was privatized and land at least risk of biodiversity loss was protected. The application revealed that new high‐elevation reserves did little to mitigate biodiversity decline, that privatization of low‐elevation land further jeopardized the most vulnerable biodiversity in lowland native habitats, and that outcomes of land reform for biodiversity deteriorated over time. Further development of robust achievement measures is needed to encourage more accountable biodiversity conservation decisions.